Multilateral cooperative compliance models: a special reference to the European Trust and Cooperation Approach (ETACA). (Revista de Estudios Europeos, 2026)
Co-operative tax compliance has emerged as a possible solution to the challenges and needs in the current tax context. In recently times, multilateral initiatives with co-operative roots have begun to be developed that aim to take a further step in this direction. The most relevant are ICAP in the OECD area and, recently, ETACA at EU level. Although their development is still in its early stages, it is already possible to observe some effects derived from their practical implementation.
Keywords: ICAP; OECD; EU; multilateral; co-operative compliance